Histomorphological Study on Prenatal Development of Spleen in Partridge (Alectoris Chukar) - Sohrab Heydarian; Iraj Pousty; Hamid Reza Moradi (Negah Institute for Scientific Communication, 2018)
Introduction: Phasianidae is a non-migratory group of birds belonged to partridges family. One of the well-known species of partridge is Alectoris chukar, which is a medium-sized bird, larger than quails and smaller than pheasants. They are native to Asia, Africa, Europe and the Middle East and belong to the category of gallinaceous birds. Understanding the physiology and immunology of the lymphoid system is incomplete without knowledge of its basic structure that we are going to examine it in these birds.  Methods: Histomorphological studies were conducted on the spleen of 60 fertilized eggs from the healthy Alectoris chukar birds. Eggs were opened and the spleens of Embryonic Day (ED) 10 to 22 were dissected by dissecting microscope. Gross morphological parameters were studied immediately after collection of samples and then the spleen samples were fixed in Bouin's solution. After tissue processing, spleens were embedded in paraffin and the prepared sections (5-6 μm) were stained using Hematoxylin and Eosin (H&E) method. Results: Based on our findings the capsule of spleen was formed by a thin and single layer of the mesothelial cells, on ED 12. At this time, macrophages were observed beneath the endothelium of sinusoids for the first time. The early distinction between the red and white pulp had been obvious on ED 14. The central artery was seen in white pulp of the spleen at ED 20. Reticular cells with large euchromatin nucleus and specified nucleolus were observed in the white pulp. At ED 22, there were Billroth cords in the spleen. Trabecular artery was observed in spleen of the partridge embryos at this time. Conclusion: This study was the first study on histogenesis and histological of spleen were performed in prenatal partridge.